Tobacco Marketing Conflict between Farmers and Middlemen in Palongan Village, Bluto District, Sumenep Regency - Shadiqin, Bani; D. W. P., Sucihatiningsih; Rachman, Maman (Universitas Negeri Semarang, 2023)
The existence of tobacco is intended to meet the demand for cigarette factories. The indirect marketing chain is the cause of the price game by stakeholders. This situation has led to a loss of trust in trading partners, farmers suspect that there is a selling price game being played by middlemen and warehouses. The price game creates negative prejudice to stakeholders. The aim of this research is to analyze conflicts between farmers and stakeholders and solutions for farmers to the problems that occur. This research uses a qualitative method with a phenomenological approach. Data collection was carried out by observation, interviews, and document study from related research. The results show that determining the category of tobacco can certainly trigger conflict between farmers, bandol, and factory warehouses because it affects general selling price indicators in the market. Farmers' expectations of selling prices and intimidation by bandol elements give rise to conflicting opinions about the two, thus triggering conflict. The uncertainty of tobacco prices has made some farmers use an alternative substitute for this commodity by cultivating corn.